2017
DOI: 10.1021/acs.biomac.7b01062
|View full text |Cite
|
Sign up to set email alerts
|

Cationic Poly(benzyl ether)s as Self-Immolative Antimicrobial Polymers

Abstract: Self-immolative polymers (SIMPs) are macromolecules that spontaneously undergo depolymerization into small molecules when triggered by specific external stimuli. We report here the first examples of antimicrobial SIMPs with potent, rapid, and broad-spectrum bactericidal activity. Their antibacterial and hemolytic activities were examined as a function of cationic functionality. Polymers bearing primary ammonium cationic groups showed more potent bactericidal activity against Escherichia coli, relative to terti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(61 citation statements)
references
References 63 publications
0
59
0
2
Order By: Relevance
“…Ergene and Palermo developed the first generation of selfimmolative antibacterial polymers 122 (Fig. 15).…”
Section: Emerging Sar Trendsmentioning
confidence: 99%
“…Ergene and Palermo developed the first generation of selfimmolative antibacterial polymers 122 (Fig. 15).…”
Section: Emerging Sar Trendsmentioning
confidence: 99%
“…Ph [16][17][18][19][20][21]65,67] Enzyme [23][24][25][26][27][28][29][64][65][66] Oxidative [31][32][33][34][35][36][37][38]58,59,62,69] Redox [41][42][43][44][45][46][47]62,64,[66][67][68][69] Self-immolative [50][51][52][53][54][55][56][57]68]…”
Section: Responsive Linkers Referencesmentioning
confidence: 99%
“…The stimuli-responsive self-immolative polymer concept has been used to develop sacrificial layer materials for the controlled release of actives in the presence of triggering conditions. [55] Ergene et al [56] reported the first example of a self-immolative polycation exerting a fast and broad-spectrum antimicrobial activity. The polycation comprised cysteamine-functionalized poly (benzyl ethers) with silyl end-capping, and retained antibacterial activity upon depolymerization after fluorine-specific treatment.…”
Section: Stimuli Responsive Self-immolative Materialsmentioning
confidence: 99%
“…15 Encapsulation, release and degradation studies of assembled materials offers the potential to create delivery vehicles that may enhance the formulation capability and efficacy of small molecules in a range of applications from pharmaceutical drug delivery through to agrochemicals, antimicrobials and cosmetics. 16 In each of these cases, the degradability of the building block structures to smaller subunits that may be benign, either in an in vivo context or in the wider environment, is very important and has been the aim of materials such as selfimmolative polymers 17,18 and triggers including reduction, 19 hydrolysis, 20 temperature, 21 chemical, 22 and light enhanced 23 mechanisms.…”
Section: Introductionmentioning
confidence: 99%